A new orbit for comet C/1858 L1 (Donati) - Branham, Richard Lacy (2014)
A new orbit for comet C/1858 L1 (Donati), based on 1036 observations in α and 971 in δ made between 7 June 1858 and 5 March 1859, is calculated using iteratively reweighted least squares. Residuals were weighted by the Welsch weighting function. The orbit represents a high eccentricity ellipse, e = 0.996265, with large semi-major axis, a = 154.8612 AU, and long period, P = 1927.22 yr. The residuals are relatively random, a 10.7 % chance of being random, but with a slight indication of possible nongravitational forces influencing the motion. The comet will not return until the year 3759, when it will pass 0.8442 AU from the Earth.